2016
DOI: 10.5543/tkda.2015.76128
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Surgery Complicated with Ventricular Fibrillation in A Young Patient; Inverted (Reverse) Takotsubo Cardiomyopathy

Abstract: Takotsubo cardiomyopathy (TTC), also known as left ventricular apical ballooning syndrome or stress cardiomyopathy, is characterized by transient left ventricular systolic dysfunction and the absence of obstructive lesion in the epicardial coronary arteries. The most common presentation is acute substernal chest pain, although occasionally dyspnea and syncope, and rarely shock with ST-segment elevation and elevated cardiac biomarkers have been observed. Inverted (reverse) TTC is a rare pattern characterized hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Unlike the post-menopausal women profile of classical type, reverse type was shown to be significantly associated with younger age and mental or physical stress rather than catecolamine excess [11,18]. Of note, death was more common in men than women with TTS [11].…”
Section: Diagnosismentioning
confidence: 78%
See 1 more Smart Citation
“…Unlike the post-menopausal women profile of classical type, reverse type was shown to be significantly associated with younger age and mental or physical stress rather than catecolamine excess [11,18]. Of note, death was more common in men than women with TTS [11].…”
Section: Diagnosismentioning
confidence: 78%
“…These symptoms are more likely to occur with less common clinical subtypes other than apical ballooning. Reverse (inverted) TTS was shown to present at a younger age and with fatal ventricular arrhythmias [18].…”
Section: Historymentioning
confidence: 99%
“…Deniz et al operated on a 92-year old patient under spinal anesthesia for transurethral resectionbladder tumor (TUR-BT) and reported that TC developed at 1 hour postoperatively [6]. Demir et al reported that ventricular fibrillation developed in a 27-year old female during recovery from general anesthesia following surgery for chronic sinusitis and nasal polyps and as a result of examinations, TC was diagnosed [7].…”
Section: Discussionmentioning
confidence: 99%
“…While QTc was 680 ms [16], TdP did not occur during monitoring. She received cardioversion because of hemodynamic compromise due to VT. On followup, her QTc was 400 ms. Demir, Babur Güler, Güler, Güneş, and Kızılırmak [17] described a 27-year-old healthy woman admitted for endoscopic sinus surgery. She developed VF during recovery from anesthesia, treated with defibrillation.…”
Section: Ventricular Tachycardia Ventricular Fibrillation and Othermentioning
confidence: 99%
“…TTC tends to occur more frequently in postmenopausal women, especially after a recent stressful episode [11,13,16,19]; however, younger women are also at risk [14,17,21], and incidence in men continues to increase every day [18,20]. Emotional stress is arguably the most common trigger.…”
Section: Ventricular Tachycardia Ventricular Fibrillation and Othermentioning
confidence: 99%